Pengaruh Aplikasi Pupuk Hayati VP3 bersama Kompos Dibandingkan Dengan Pupuk NPK Terhadap Produksi Tanaman Kacang Hijau (Vigna radiata L.) dan Viabilitas Bakteri Tanah - Wiwit Nur Hidayah; Indiyah Murwani; Novi Arfarita (Universitas Islam Malang, 2020)
Biofertilizer is a living microorganism that is useful for increasing soil fertility and the quality of production of a plant. Biofertilizer VP3 which has been formulated and developed in previous studies contains 3 soil bacteria, namely N free fixing bacteria, phosphate and bacterial solvents EPS producing bacteria (exopolysaccharide). VP3 biological fertilizer that is applied with compost can be used to degrade compost into humus (fine particles / colloids) which plays an important role for microorganisms, soil and plants with applications for a certain period. The design used was a randomized block design (RBD) with 8 treatments 3 replications. Provision of biofertilizers and NPK fertilizers affect the viability of soil bacteria. The treatment of VP3 biofertilizer with compost and combined with NPK fertilizer 25%, 50% and 75% had yields (number of pods and weight of dry seeds) green beans which were not significantly different or not significant, while biological fertilizer treatment with compost with NPK combination 25 % has the yield of green beans which is not significantly different from the treatment of biofertilizers and compost only. The treatment of VP3 biofertilizer with compost alone without a combination of NPK fertilizer is more economical for farmers. Keywords: biofertilizer, compost, green beans, viability bacteria, NPK fertilizer